Brain activity and Alzheimer's disease: a complex relationship. (19th July 2016) - Hansson, Oskar; Gouras, Gunnar
Abstract : This scientific commentary refers to 'Dynamic relationships between age, amyloid-β deposition, and glucose metabolism link to the regional vulnerability to Alzheimer's disease', by Oh et al. (doi:10.1093/brain/aww108 ).